Computational flow analysis of a single peristaltic wave propagation in the ureter. (October 2021) - Keni, Laxmikant G.; Hayoz, Mattias Jan; Khader, Shah Mohammad Abdul; Hegde, Padmaraj; Prakashini, K.; Tamagawa, Masaaki; Satish Shenoy, B.; Hameed, B.M. Zeeshan; Zuber, Mohammad
Highlights: The study involves CFD analysis of the peristaltic motion of urine bolus in a ureter Peristaltic contraction results in high-pressure formation at the bolus and negative pressure at the neck. The wall shear near the contracted throat region will decrease with the propagation of the peristalsis wave towards the urinary bladder. The magnitude of the pressure gradient is high at the ureter wall and along the ureter axis around the moving contracted region, which decreases as the wave propagates towards the urine bladder. Abstract: Background and objective: The bladder receives the urine from the kidney and ureter. The series of peristaltic waves facilitate urine transport to the bladder. The peristaltic flow in the ureter is associated with fluid trapping and material reflux, which may cause an increase in bladder pressure. It is difficult to visualize the complex peristalsis phenomenon, in the ureter using image and radiography experiments. A numerical simulation will help in the understanding of urine bolus formation and its effect on the ureter wall. Methods: A three-dimensional computational fluid dynamic analysis is carried out to understand the flow physics associated with bolus formation and the effect of reflux on the ureter. ANSYS-CFX, a commercially available computational dynamics package is used to simulate the peristalsis. A single sinusoidal peristaltic wave traveling along a circular tube will yield the velocity, pressure, wall shear stress distributions inside the ureter. Results: The propagation of the peristaltic wave results in the backflow of urine near the inlet at the beginning of the flow. As the wave propagates towards the outlet, the flow rate decreases. It is observed that pressure distribution along the ureter axis will deteriorate towards the outlet. The contraction produces a very high-pressure gradient which causes the urine backflow. The trapping and the bolus formation cause a significant rise in bolus pressure, simultaneously developing negative pressure at the contraction neck. Conclusions: The effect of peristalsis on the ureter biofluid dynamic behavior of the ureter is visualized in this study. It is established that the peristaltic contraction results in high-pressure formation at the bolus and negative pressure at the neck. It was found to be a maximum of 1.1 Pa at the bolus center and —1.13 Pa at the neck region. At the ureter pelvis junction, a higher wall shear of 0.095 Pa is observed as the wave starts to propagate. The velocity vectors show that the trapping of urine causes reflux and results in an adverse pressure gradient near the wall. A maximum pressure gradient of 485 Pa/meter was observed at the contraction of the ureter wall.